Who tends to consume most tobacco in China? Analysis of income-related inequality in tobacco consumption among elderly people. (December 2017) - Si, Yafei; Su, Min; Zhou, Zhongliang
Abstract: Background: The burden of non-communicable diseases burden in China is enormous, with tobacco consumption a leading risk factor for the most prevalent NCDs. Therefore, understanding pattern of socioeconomic equalities of tobacco consumption will help to design targeted public health control measures. We aimed to investigate who tends to consume most tobacco in China. Methods: Nationally representative data from the 2013 China Health and Retirement Longitudinal Study (CHARLS) included smoking information on 17 663 respondents aged 45 years and older. Smoking prevalence and smoking quantities were defined to capture tobacco consumption. Using concentration index (defined as twice the area between the concentration curve and the line of equality), we estimated income-related inequality of tobacco consumption grouped by gender. The inequality of tobacco consumption was further decomposed into each determinant's specific contribution on using probit regression analysis and Ordinary Least Squares (OLS) regression models. Findings: About 16·03% of respondents consumed tobacco. By sex, 8449 men (29·65%) and 9213 women (3·54%) consumed tobacco. Furthermore, we found a significant pro-rich inequality of tobacco consumption. The concentration index of smoking incidence was 0·0438 (0·0412 for men; −0·0393 for women). The concentration index of smoking quantities among people who smoke was 0·0385 (0·0333 for men; 0·0381 for women), whereas the concentration index of smoking quantities in the whole population was 0·0748 (0·0675 for men; −0·0044 for women). Most of the inequality can be explained by education attainments, age, geographical areas, and economic status. Interpretation: Sex, education attainments, age, geographical areas, and economic status were strong predictors of tobacco consumption in China. Public health policies need to be targeted towards the less educated people and elderly people. Both the pattern and magnitude of inequality varied greatly between men and women, and public policies for tobacco control in men should be strengthened at southern-central and northern areas of China, whereas public policies for women should be strengthened in the eastern and northeastern areas of China. Funding: Research Program of Shaanxi Soft Science (2015KRM117), Shaanxi Provincial Youth Star of Science and Technology in 2016, Basic Scientific Research Funding of Xi'an Jiaotong University (SK2015007), and National Program for Support of Top-notch Young Professionals and China Medical Board (15-227).